Antibacterial activity of Indonesian Bidara Upas Tuber (Merremia Mammosa L.) against pathogen bacteria - Nurrosyidah, Iif Hanifa; Oktalia Eka Saputri, Ervina; Mufidatunnisa, Sayyidah; Anwari, Farida; Ningsih, Arista Wahyu (Gaceta Médica de Caracas, 2022)
Introduction: Infectious diseases are still a problem in developing and tropical countries such as Indonesia. This study aims to determine whether the antibacterial substances contained in Bidara Upas tubers affect the growth of Streptococcus sp., Pseudomonas aeruginosa, Escherichia coli Extended-spectrum β-lactamase and Methicillin resistance Staphylococcus aureus (MRSA).